Pengembangan lembar kerja mahasiswa (LKM) untuk menumbuhkan motivasi belajar pada matakuliah kalkulus lanjut di masa pandemi Covid-19 - Taqwa, Muhammad (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The Corona Virus Disease pandemic (Covid-19) requires that conduct online learning and independently including advanced calculus courses. Learning requires students to have a strong motivation to study. The development of Student Worksheets (SW) is a strategy that can foster student motivation. The purpose of this study was to develop a valid, practical and effective SW in growing student motivation. This kind of research was development research, namely the development of SW with the Plomp model: (1) initial investigation, (2) design, (3) realization/ construction, (4) tests, evaluations and revisions, (5) implementation. The subjects of this research were students of Mathematics Education Program in STKIP Andi Matappa. Research instruments: (1) SW validation sheet; (2) practicality sheets of SW; (3) student learning motivation questionnaire. The results of the study: (1) the content validity score of the SW is included in the very high category, (2) the practicality score of the SW has very practical criteria; (3) the median of student learning motivation who are given SW treatment is at least in enough category that mean the treatment of LKM giving effectively foster student motivation. This shows that advanced calculus SW that has been developed meets valid, practical and effective to foster student motivation